Trótula y un poema médico de la Collectio Salernitana. Parte 1: De secretis mulierum - Alonso Guardo, Alberto (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
The aim of this paper is to study in detail the relationship between the work traditionally attributed to “Trotula” and the first chapter (De secretis mulierum) of an anonymous medical poem published in the Collectio Salernitana: De secretis mulierum, de chirurgia e de modo medendi libri septem
Keywords: Salerno; Medieval Latín; Medieval medicine; Latin poetry